The Role of Globalization and Media in Modern Society - Drakulovska Chukaleska, Marija; Dragovikj, Anica (University Goce Delchev, Shtip, 2017)
This work is especially focused on a theoretical interaction between globalization and media as two mutually connected questions and investigates their reciprocal working in modern time. In this paper, we have tried to situate the power of globalization and media currently, it is also incumbent on us to attempt to predict the future of globalization and media. Globalization and media are phenomena which, in a great measure, signify every modern society and culture. In the last few decades, in the social science, a great interest is notified for them especially in the sociology science. Sociologists such as Roland Robertson, Ulrich Beck, Anthony Giddens, Manuel Castells are observe these phenomena as a dynamic process that is built on the base of their mutual connection and dependence and through them explains the changes that happen in the separated sociocultural realities.
Keywords: globalization, media, communications, changes, media imperialism, global local vice versa, world